Eight different bioactivity profiles of 40 cinnamons by multi-imaging planar chromatography hyphenated with effect–directed assays and high-resolution mass spectrometry. (30th September 2021) - Sumudu Chandana, N.G.A.S.; Morlock, Gertrud E.
Highlights: Valorization of foods visualized by profiling of cinnamon samples for bioactive compounds. Multi-imaging and effect-directed profiles highlighted multi-potent compounds. Effects revealed against microbials, α/β-glucosidase, acetyl-/butyrylcholinesterase, tyrosinase, oxidation. Characterization of multi-potent compounds by high-resolution mass spectrometry. Bioanalytical hyphenation suited for routine screening of product quality. Abstract: Spices contain plenty of bioactive compounds, used to valorize foods. However, product quality may be affected by contaminations and adulterations along the global production chain. A newly developed multi–imaging in combination with bioactivity screening directly pointed to individual multi–potent compounds. For cinnamon as prominent example, the multi–imaging results provided a wealth of new information on their effects and clearly visualized the valorizing potential of cinnamon to foods. The separation focus was in the mid–polar to apolar range. Eight effect–directed assays (EDA, i.e. one radical scavenging, two biological and five biochemical assays) were performed in situ the high–performance thin–layer chromatography (HPTLC) adsorbent. Several multi–potent compound zones were revealed and further characterized by high–resolution mass spectrometry (HRMS), highlighting the bioactive potential of cinnamaldehyde, cinnamic acid, benzoic acid, coumarin, linoleic acid, oleic acid, stearic acid, palmitic acid, caproic acid, and linalool oxide. This HPTLC–UV/Vis/FLD–EDA–HRMS profiling provided comprehensive information on product quality and safety.